Building-to-grid flexibility: Modelling and assessment metrics for residential demand response from heat pump aggregations. (1st January 2019) - Zhang, Lingxi; Good, Nicholas; Mancarella, Pierluigi
Highlights: Novel metrics are designed to quantify building-to-grid demand response flexibility. Power and energy paybacks following load curtailment can vary from 0% to 50% Dwellings with high thermal inertia show a smaller but longer payback. Hybrid heating system reduces power and energy paybacks to less than 20% Abstract: Increased flexibility has been identified as a key requirement in future power systems. Much flexibility could be provided by energy vectors other than electricity. In particular heat may be a valuable source of flexibility, as electrification of space and water heating introduces highly flexible resources such as electric heat pumps. However, current methods for assessing aggregated demand side flexibility, particularly from residential buildings, may not be adequate given the variety of different grid services that flexibility may be used to provide to different stakeholders, and considering relevant comfort constraints. On these bases, in this work several metrics, relevant to different stakeholders, are introduced to quantify building-to-grid demand response flexibility from heat pump aggregations. Specific control algorithms for the aggregations are also proposed and tested through a multi-energy residential energy consumption tool. A number of case studies are carried out to demonstrate the value of the proposed metrics and algorithms, especially in relation to flexibility exploitation with long sustain times (e.g., reserve services), which can noticeably affect user comfort. Our results indicate that the payback behaviour of heating units following a demand response event can vary substantially with different types of dwellings. More specifically, the power payback is negligible in dwellings with high thermal inertia, while the power and energy payback can reach 10% and 50%, respectively, in dwellings with low thermal inertia. The benefits from hybrid (electric + gas) heating, which can reduce energy payback and comfort loss, are also demonstrated. For instance, in a cluster of dwellings with low thermal inertia, the energy payback following a DR event is reduced from 50% to 20% and the maximum comfort loss of the participants is decreased from 1.6 °C to 0.5 °C.